2012
DOI: 10.3346/jkms.2012.27.10.1208
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of an Esophageal Fish Bone Foreign Body fromChromis notata

Abstract: Damselfish Chromis notata is a small fish less than 15 cm long and it is widespread in the Indo-Pacific Ocean. Of all the cases of fish bone foreign body (FBFB) disease at our hospital, a damselfish FBFB was very common, and a specific part of the bone complex was involved in the majority of cases. This study was performed to evaluate the clinical characteristics of damselfish FBFB in Jeju Island. We retrospectively reviewed the medical records from March 2004 to March 2011 for foreign body diseases. Among 126… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…This result may be due to the small sample size and is consistent with a previous report. In a study by Kim and Song, 20 only two patients underwent surgery due to abscess formation. In those cases, the durations of time between ingestion and hospital arrival were 3 and 5 days.…”
Section: Discussionmentioning
confidence: 99%
“…This result may be due to the small sample size and is consistent with a previous report. In a study by Kim and Song, 20 only two patients underwent surgery due to abscess formation. In those cases, the durations of time between ingestion and hospital arrival were 3 and 5 days.…”
Section: Discussionmentioning
confidence: 99%
“…In South China, fish bone ingestion is most common (60%) among the FB diseases and becomes more prevalent with time [ 22 ]. In Korea, FFB is most common (46% to 72.3%) in upper gastrointestinal FB disease [ 23 - 26 ]. Sex distributions varied among centers.…”
Section: Fish Bone Foreign Body In the Esophagus And Pharynxmentioning
confidence: 99%
“…For example, fish stew has higher risk of esophageal FFB (Kim et al 2015). In study by Kim and Song showed that Damselfish and Armorchlad rockfish are top two causative FFB in Korea due to its unique bone shape and popular fish for Korean dishes (Kim, & Song 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Among all complications, esophagus perforation is most common (Nandi, & Ong, 1978). In FFB, more than half will develop esophageal penetration or perforation (Kim, & Song, 2012). Complications develop more frequently with longer duration of impaction (>24 hours), bone type, and longer bone length (>3 cm) (Marco de Lucas et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation